PENGARUH SOCIAL DISTANCING TERHADAP KEREKATAN HUBUNGAN ANTAR MAHASISWA STT GKE - Idrus Sasirais; Enta Malasinta; Ripaldi (Jurnal Teologi Pambelum, 2021)
The current coronavirus disease 2019 (COVID-19) pandemic, which has been spread all over the world since the beginning of 2020, has inevitably impacted all activities of the Indonesian nation, including those in the education sector. STT GKE is included. To prevent Covid-19 transmission spread widely, the government requires people to implementing social distancing (also called physical distancing). All universities, including STT GKE, have been mandated by the governments to close their campuses and to move learning activities online. Although the implementation of the health protocol was effective in controlling the spread of the disease, it hurts the students. Quantitative research conducted by the STT GKE research team from August to December 2000 concluded that the implementation of the protocol (social distancing, including online learning) caused the cohesion among students to get lost.